Análise de resíduo de disparo de armas de fogo utilizando ICP-MS: caracterização de munições limpas - Costa, Rayana Alvarenga (2016)
Given the strong relationship between the crimes of murder and the use of firearms in Brazil, Forensic Ballistics is an important tool to detect waste generated by shooting firearms (GSR -gunshot residues) in the hands of a suspect , helping to determine the authorship of a shot. Among the types of ammunition, clean ammunition was developed in the last decade to minimize exposure of the shooters to lead (Pb), as in conventional ammunition, this element and the Ba and Sb present significativas1 concentrations. Studies show difficulties in GSR detection clean ammunition by energy dispersive spectroscopy coupled with scanning electron microscopy (SEM / EDS) and residuográfico test, thus modern analytical techniques such as mass spectrometry with inductively coupled plasma (ICP-MS) has being used as a quick analysis for the detection of chemical elements present in GSR, since a high sensitivity, selectivity and multielement character. Thus, the objective of this study was to evaluate the applicability of ICP-MS technique to quantify the GSR coming from clean ammunition (from the English "clean range ammunition") using caliber .40 pistol and .38 depending on the number of shots (n = 1-7 and n = 1-5). The GSR were collected in the regions of the clamp-palmar and dorsal clamp and evaluated on both hands (right and left). The results were compared with classic techniques in forensic ballistics: colorimetric assay using sodium rhodizonate (residuográfico) and SEM / EDS. Negative results were observed for Pb and Ba using residuográfico test for GSR analysis clean ammunition shots to 7. The analysis by SEM / EDS was performed on the GSR produced from n = 7 (.40 caliber pistol) and n = 5 (.38 revolver) of clean ammunition. Photomicrographs showed that the GSR produced from clean ammunition presents no defined as the morphology of conventional ammunition GSR. In addition, EDS results of the particularly identified elements as C, O, K, Al, S, Si, Cu, Zn, Ti, Cr, Cl, Mo, Sr and Fe. Unlike convencionas methods, ICP-MS technique showed positive results for Pb, Ba and Sb with maximum concentration of 2.64 µg·L-1(± 0.60) 10.9 µg·L-1(± 5.44) and 0.119 µg·L-1(± 0.02) to40 pistoland 4.59 µg·L-1(± 1.8), 1.95 µg·L-1(± 1.1) 0.099 µg·L-1(± 0.07 ) to .38 revolver. Besides them, elements such as Al, Ti, Cr, Mo, Cu, Zn and Sr were also detected in the clean ammunition GSR. It was observed that with increasing number of shots was in the concentration of all investigated elements and suggested that Al, Sr, Zn and Cu may be used as markers for new GSR clean ammunition. Therefore, the ICP-MS technique showed promising results and proved adequate for GSR analysis of clean ammunition.